European experts consensus statement on cystic tumours of the pancreas - Del Chiaro, Marco; Werner, Jens (Digestive and liver disease, 2013)
Cystic lesions of the pancreas are increasingly recognized. While some lesions show benign behaviour (serous cystic neoplasm), others have an unequivocal malignant potential (mucinous cystic neoplasm, branch- and main duct intraductal papillary mucinous neoplasm and solid pseudo-papillary neoplasm). European expert pancreatologists provide updated recommendations: diagnostic computerized tomography and/or magnetic resonance imaging are indicated in all patients with cystic lesion of the pancreas. Endoscopic ultrasound with cyst fluid analysis may be used but there is no evidence to suggest this as a routine diagnostic method. The role of pancreatoscopy remains to be established. Resection should be considered in all symptomatic lesions, in mucinous cystic neoplasm, main duct intraductal papillary mucinous neoplasm and solid pseudo-papillary neoplasm as well as in branch duct intraductal papillary mucinous neoplasm with mural nodules, dilated main pancreatic duct >6mm and possibly if rapidly increasing in size. An oncological partial resection should be performed in main duct intraductal papillary mucinous neoplasm and in lesions with a suspicion of malignancy, otherwise organ preserving procedures may be considered. Frozen section of the transection margin in intraductal papillary mucinous neoplasm is suggested. Follow up after resection is recommended for intraductal papillary mucinous neoplasm, solid pseudo-papillary neoplasm and invasive cancer.
Gesehen am 10.12.2020